PENGARUH STRUKTUR MODAL, KONVERGENSI IFRS DAN TAX PLANNING TERHADAP NILAI PERUSAHAAN (Studi kasus pada perusahan manufaktur sub sector makanan dan minuman periode 2016-2020 yang terdaftar di BEI) - Aniah Aniah; Sry Ayem (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to determine the effect of capital structure, ifrs convergence and tax planning on firm value (a case study on a food and beverage sub-sector manufacturing company for the period 2016-2020 listed on the IDX). The type of research used in this study is survey research with a quantitative descriptive approach. . The data processed is the summary Capital Structure of IFRS, Tax Planning and Company Value of the Food And Baverages Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period which is obtained from the annual report (Annual Report). Sampling in this study used a non-probability sampling technique, namely the purposive sampling technique, where data was selected based on certain criteria that were in accordance with the research objectives. en) and library research (taken from journals, books, and the internet). Based on the results of the processed data, the significance value of t from the Capital Structure (DER) variable is 0.000 and has a regression coefficient value of 0.604. Because the significant value of t is less than 0.05, it is stated that the Capital Structure (DER) has a positive and significant effect on firm value. International Financial Reporting Standard (IFRS) is 0.485 and has a regression coefficient value of 0.005. Due to the significant value of t greater than 0.05, this means that the International Financial Reporting Standard (IFRS) variable has no effect on firm value. Tax planning (ETR) is 0.219 and has a regression coefficient of 0.005. Due to the significant value of t greater than 1.043, this means that the Tax planning (ETR) variable has no effect on firm value